A betlehemes pasztorációja - BODÓ, Sára (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
The Pastoral Message of the „Betlehemes” Custom. Human life has always been defined by one’s relation to time. Christianity sees the Nativity as a turning point in time: the chairos occurred in the aion. In Greek mythology there is a distinction between chronos (the continuous time) and chairos (the opportune moment). The salvation story is linked to chairos moments ordained by God. We are nowadays racing against time, however, time does not only pass, but – in terms of chairos moments – it also arrives. Time can be taken in; the time thus received holds many gifts and gives a particular dignity to human life. Human beings are able to take in things at least in two ways: one necessarily takes in its environment from the fetal stage, but this reception is influenced by the desire for love and acceptance. The possibilities of celebrating Christmas can aid the experience of reception. The so called “betlehemes”, i.e. telling the Nativity story in songs and verse and preparing the setting for this has become a veritable hungaricum. The preparations for this customs and the family games connected to it have a pastoral impact. The texts display a meeting of the sacred and the profane, the appearance of the holy in the profane world. This can also be seen in the ceramics portrayal of the Nativity by an unknown artist, which can aid the reception of the Christmas story.